Research of vein-protective effect of the preparation "Agsular”® on the models of 106 vascular pathology - V. V. Kostyro; Ya. A. Kostyro; S. A. Lepekhova; I. V. Babushkina; I. A. Shurygina; V. K. Stankevich; B. A. Trofimov (Acta Biomedica Scientifica)
Varicose disease is the most common vascular pathology of lower extremities that causes development of chronic venous insufficiency (CVI). Modern Russian pharmaceutical market of medicines external application used in phlebology is mainly presented by expensive imported medicines. That's why development of original Russian high-effective and. available medicines for prevention, and. treatment of chronic venous insufficiency is an actual problem of medical and. pharmaceutical sciences. Pharmacologically active substance 'Asgular®" that has hypolipidemic and anticoagulant activity was developed in A.E. Favorsky Irkutsk Institute of Chemistry SB RAS as the result of chemical modification of polysaccharide of Siberian larch. Original pharmaceutical compositions (preparation. "Asgular®") in solid and. liquid medicinal forms for external application in forms of hydrophilic gel and rectal capsules with hydrophilic gel were developed on the basis of that active substance. Veinprotective effect of "Agsular®" preparation was studied on the models of vascular pathology. It was determined. that antiinflammatory activity and. anti-transudative effect — decrease of vessels' permeability and increase of their walls' tone — were of most importance in the mechanism of veinprotective effect of the preparation "Agsular"®. Anti-inflammatory activity is developed in decrease of intensity of neutrophil infiltration in wound, area and. in anti-exudative effect that is presented by the decrease of stroma and cell hypostases. Thus our researches indicates prospectivity of use of "Agsular'® preparation for prevention and. treatment of chronic venous insufficiency and varicosis in particular.